Efficient photocatalytic degradation of bisphenol A on 2D-3D spherically hierarchical structure Zn5In2S8 - Zhang, Zongwen; Zhang, Yi; Han, Huili; Ikreedeegh, Riyadh Ramadhan; Shah, Syed Shoaib Ahmad; Tayyab, Muhammad (Frontiers in Chemistry, 2025)
Bisphenol A (BPA) poses a significant environmental threat due to its widespread use as an industrial chemical and its classification as an environmental endocrine disruptor. The urgent need for effective BPA removal has driven research toward innovative solutions. In this study, we present the synthesis and application of a novel 2D-3D spherically hierarchical Zn5In2S8 (ZIS) photocatalyst for the photocatalytic degradation of BPA under visible light for the first time. Compared to the conventional g-C3N4 photocatalyst, ZIS exhibits enhanced optical and electrical properties, leading to remarkable photocatalytic performance, with an apparent reaction rate constant of 2.36 h⁻1, 6.56 times greater than that of g-C3N4. This efficacy allows for the degradation of 99.9% of BPA in just 2 h. The photocatalytic mechanism of ZIS was elucidated through various material characterizations and photoelectrochemical assessments, demonstrating improved light absorption and efficient charge separation as key factors facilitating BPA degradation. Notably, ZIS maintains high photocatalytic activity and stability over multiple cycles, indicating its potential as a sustainable photocatalyst. These findings not only contribute to the development of efficient photocatalysts for environmental remediation but also underscore the significant role of Zn5In2S8 in photocatalysis and solar energy conversion.